The Representation of Mental Illness in The Movie â€œMaâ€ : An Application of Jungâ€™s Psychoanalysis - Sarni F; Muarifuddin Muarifuddin; Eva Gultom (ELITE: Journal of English Language and Literature, 2021)
Ma is a 2019 Psychological Horror movie that was directed by Tate Taylor and produced by Universal Pictures which was released in 2019. This study focuses on the main character. The objective of the study is to explain the representation of Carl Gustav Jung’s Psychoanalysis in the movie Ma. The data used the descriptive qualitative method. Carl Gustav Jung’s Psychoanalysis was used as a tool of analysis to explain the findings. The result in this study concerns Ma’s personality upbringing, she utilizes her persona to mislead the teenagers into fulfilling her desires to get her revenge on her old friends. Sue Ann's shadow gets her into a dark place in her life. She tortured the teenagers and killed Ben and Mercedes without acknowledging her bad behavior. She does not show empathy to her victims.